2018
DOI: 10.4103/ijmr.ijmr_2020_17
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on association between smokeless tobacco & cardiovascular diseases

Abstract: Background & objectives:The association of smokeless tobacco (SLT) with cardiovascular diseases has remained controversial due to conflicting reports from various countries. Earlier meta-analyses have shown significantly higher risk of fatal myocardial infarction and stroke in SLT users. However, the risk of hypertension (HTN) with SLT products has not been reviewed earlier. This systematic review was undertaken to summarize the evidence available from global literature on the association of SLT with cardiovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 63 publications
2
12
1
2
Order By: Relevance
“…Diabetes mellitus is likely to develop among tobacco users. 4,8,10,[14][15][16] the prevalence of diabetes mellitus was lower among the above studies compared to the present study findings. The OR for developing diabetes Mellitus was found to be in the range of 1.3 to 4.9).…”
Section: Risk Of Chronic Morbidities and Factorscontrasting
confidence: 49%
See 3 more Smart Citations
“…Diabetes mellitus is likely to develop among tobacco users. 4,8,10,[14][15][16] the prevalence of diabetes mellitus was lower among the above studies compared to the present study findings. The OR for developing diabetes Mellitus was found to be in the range of 1.3 to 4.9).…”
Section: Risk Of Chronic Morbidities and Factorscontrasting
confidence: 49%
“…workers (nurses), it was found that female smokers were 25% more likely to develop CVD than male workers. 3,4 Prevalence of diabetes mellitus was high in this study (41.2%). Diabetes mellitus is likely to develop among tobacco users.…”
Section: Risk Of Chronic Morbidities and Factorsmentioning
confidence: 48%
See 2 more Smart Citations
“…Figyelembe véve, hogy a magyar lakosság egészségi állapota a más európai országokban élőkénél kedvezőtlenebb képet mutat, az egyik legfontosabb teendő a szívés érrendszeri betegségek kialakulásában szerepet játszó kockázati tényezők csökkentése, legfőképpen primer prevenciós eszközökkel [41,48,49]. Az elsődleges megelőzésben fontos szerepe lehet a készülő Nemzeti Népegészségügyi Stratégiának is.…”
Section: Megbeszélésunclassified